Single Cell RNA Sequencing Identifies HSPG2 and APLNR as Markers of Endothelial Cell Injury in Systemic Sclerosis Skin - Apostolidis, Sokratis A.; Stifano, Giuseppina; Tabib, Tracy; Rice, Lisa M.; Morse, Christina M.; Kahaleh, Bashar; Lafyatis, Robert (Frontiers in Immunology, 2018)
Objective: The mechanisms that lead to endothelial cell (EC) injury and propagate the vasculopathy in Systemic Sclerosis (SSc) are not well understood. Using single cell RNA sequencing (scRNA-seq), our goal was to identify EC markers and signature pathways associated with vascular injury in SSc skin. Methods: We implemented single cell sorting and subsequent RNA sequencing of cells isolated from SSc and healthy control skin. We used t-distributed stochastic neighbor embedding (t-SNE) to identify the various cell types. We performed pathway analysis using Gene Set Enrichment Analysis (GSEA) and Ingenuity Pathway Analysis (IPA). Finally, we independently verified distinct markers using immunohistochemistry on skin biopsies and qPCR in primary ECs from SSc and healthy skin. Results: By combining the t-SNE analysis with the expression of known EC markers, we positively identified ECs among the sorted cells. Subsequently, we examined the differential expression profile between the ECs from healthy and SSc skin. Using GSEA and IPA analysis, we demonstrated that the SSc endothelial cell expression profile is enriched in processes associated with extracellular matrix generation, negative regulation of angiogenesis and epithelial-to-mesenchymal transition. Two of the top differentially expressed genes, HSPG2 and APLNR, were independently verified using immunohistochemistry staining and real-time qPCR analysis. Conclusion: ScRNA-seq, differential gene expression and pathway analysis revealed that ECs from SSc patients show a discrete pattern of gene expression associated with vascular injury and activation, extracellular matrix generation and negative regulation of angiogenesis. HSPG2 and APLNR were identified as two of the top markers of EC injury in SSc.